(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Investment plays an important role in economic activity, especially with current transformations. The means and methods vary according to the investor’s vision and tendencies. The study dealt with the concept of return and risk and how to measure them, and that the problem of research lies in one of the problems facing investment, especially in the field of trading shares in the Iraqi market for securities, which may result from the poor diversification of the investment portfolio, as well as the stability of return and risk, Variance in the rates of values of the prices of trading shares. The research aims to form a clear idea of the principle of portfolio in the field of investment, as well as fluctuations in the values of the Iraqi stock market and the possibility of highlighting the indicators through the use of statistical methods to describe the phenomenon, through the hypothesis of research. The study concluded the most important correlation between the values of exchange rates of shares traded for Iraqi banks, which vary in values of values of the prices of the circulation of those shares, and recommended to investigate the reasons and to identify the differences resulting from individual securities and financial portfolio containing several securities. To diversify and include some non-risky assets